Modelling Environmental Impact of Sea Dike and Toll Road in Semarang-Demak Indonesia Based on Satellite Imagery Data - Widjonarko, Widjonarko; Purnaweni, Hartuti; Maryono, Maryono; Soeprobowati, Tri Retnaningsih (Geoplanning: Journal of Geomatics and Planning, 2025)
The construction of the sea dike and Semarang-Demak toll road has severed the mangrove ecosystem inside the dike, as well as increased greenhouse gas impacts due to transportation activities and the growth of built-up areas around the dike and toll road. The aim of this research is to formulate a regression model based on spatial data that can be used to measure the impact of transportation activities and building intensity on LST. The data used in this study are the number of motorized vehicles crossing the main roads in Semarang City and LST obtained from the Landsat 8 thermal infrared sensor band in 2013 and 2019. This research utilizes Geographic Information System, Remote Sensing, and statistical methods to model the environmental impact of the sea dike and toll road development. This model used to predict the environmental impact of the sea dike and Semarang-Demak Toll Road in the future. The result shows that the increase in the number of motorized vehicles and building intensity has a high contribution to LST. Every additional 1,000 passenger cars on a road will make LST increase from 0.0150C to 0.0380C, whereas every 10% increase in land intensity will make LST increase by 0.030C. In addition, there is an increase in the LST value of 300C from 260C previously. This model is expected to provide input for each stakeholder to mitigate the potential environmental impacts of the Semarang-Demak Sea dike and toll road in the future, and hope that the Semarang-Demak Sea dike.